The influence of midazolam on heart rate arises from cardiac autonomic tones alterations in Burmese pythons, Python molurus - Lopes, Ivã Guidini [UNESP]; Armelin, Vinicius Araújo; Braga, Victor Hugo da Silva [UNESP]; Florindo, Luiz Henrique [UNESP] (Elsevier, 2017)
The GABAA receptor agonist midazolam is a compound widely used as a tranquilizer and sedative in mammals and reptiles. It is already known that this benzodiazepine produces small to intermediate heart rate (HR) alterations in mammals, however, its influence on reptiles' HR remains unexplored. Thus, the present study sought to verify the effects of midazolam on HR and cardiac modulation in the snake Python molurus. To do so, the snakes' HR, cardiac autonomic tones, and HR variability were evaluated during four different experimental stages. The first stage consisted on the data acquisition of animals under untreated conditions, in which were then administered atropine (2.5 mg kg− 1; intraperitoneal), followed later by propranolol (3.5 mg kg− 1; intraperitoneal) (cardiac double autonomic blockade). The second stage focused on the data acquisition of animals under midazolam effect (1.0 mg kg− 1; intramuscular), which passed through the same autonomic blockade protocol of the first stage. The third and fourth stages consisted of the same protocol of stages one and two, respectively, with the exception that atropine and propranolol injections were reversed. By comparing the HR of animals that received midazolam (second and fourth stages) with those that did not (first and third stages), it could be observed that this benzodiazepine reduced the snakes' HR by ~ 60%. The calculated autonomic tones showed that such cardiac depression was elicited by an ~ 80% decrease in cardiac adrenergic tone and an ~ 620% increase in cardiac cholinergic tone – a finding that was further supported by the results of HR variability analysis.
Keywords: Autonomic nervous system; Benzodiazepine; Heart rate; Midazolam; Python molurus